OPTIMIZING THE IMPLEMENTATION OF DISCHARGE PLANNING IN X GENERAL HOSPITAL JAKARTA: DOI: https://doi.org/10.35654/ijnhs.v2i1.72 - Dyah Fitri Wulandari; Rr. Tutik Sri Hariyati (Alta Dharma Publisher, 2019)
Discharge planning is a complex process aiming to prepare patients during a transition period in a hospital until they are home. One of general hospitals (X) in Jakarta has implemented discharge planning, but it is not optimally conducted. This research aims to analyze the implementation of optimizing discharge planning in X General Hospital in Jakarta. This research employed pilot study initiated by conducting assessment through questionnaire, observation, and interview. The next stages were root cause analysis by employing fishbone analysis, Plan of Action (POA) arrangement, Plan Do Check Action (PDCA) implementation, and evaluation by employing questionnaire. One of the problems of implementing discharge planning is was implementation method in which the guidance of discharge planning was not available. Therefore, standard operating procedures (SOP) and format of discharge planning were necessarily revised. After arranging the guidance draft, SOP, and format of discharge planning, the researcher socialized and tested the SOP and format of discharge planning in two inpatient rooms. The results reveal that 80% of respondents state that the arranged format of discharge planning is easily understandable, easily applicable, less complicated, not rambling, and practical. Therefore, the management of X hospital Jakarta necessarily conducts the follow-up to develop and legalize the guidance draft, SOP, and format of discharge planning. Furthermore, the management necessarily socializes them to duty nurses before the hospital applies them.